If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(1g + -4) = 3 Reorder the terms: 7(-4 + 1g) = 3 (-4 * 7 + 1g * 7) = 3 (-28 + 7g) = 3 Solving -28 + 7g = 3 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '28' to each side of the equation. -28 + 28 + 7g = 3 + 28 Combine like terms: -28 + 28 = 0 0 + 7g = 3 + 28 7g = 3 + 28 Combine like terms: 3 + 28 = 31 7g = 31 Divide each side by '7'. g = 4.428571429 Simplifying g = 4.428571429
| .75x=1017 | | 1/5(15-4p)-1/10(10p+5) | | 5x^2-50x+125=500 | | Y=3/2x+1/2 | | 30p+9q= | | -2-(-61)= | | w-(-16)=-16 | | -49=-7x+21 | | 9(x+7)+4=-9(x-2)-6 | | 12+x/9=-24 | | X/8+10=26 | | r(n)=24-5n | | 18-6x=30 | | U^2-10u+16=0 | | x^3-14x^2=-49x | | -5x+20=85 | | y=-(-1)+4(-1)+5 | | (x-2)+(x-2)+(x-2)=294 | | -45=-5x-80 | | 2x+10y=3 | | c/9-8=167 | | 100+(-3)= | | 6(3+x)=6+8x | | -24=-4x-36 | | 6x+35=125 | | -21=-30-3x | | -2*2+1= | | 1/4(-1)-1 | | 4x+65=125 | | -2*1+1= | | y=8+6 | | -30-3x=42 |